Forecast of Reliability and Durability of Complicated Power System Operation according to Generated Radio Noise - L. I. Gretchihin; V. B. Timoshevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Double electric layers of the divided electric charges arise in the places of cluster joints of various substances. Due to this phenomena dipole-type radio frequency emission is initiated. While burning various types of fuel in the combustion chambers of power systems relatively high radio-frequency emission appears as well. This emission is amplitude-modulated by a weak radiofrequency emission which is caused by mechanical and thermal effects. If a frame executes role of an aerial radiator then a radio-frequency emission is modulated as well according to oscillation frequency of the frame. Changes in frequency and intensity of combination frequencies testify to deviations of the power system from its normal operation. In accordance with the determined threshold it is possible to assume that the power system is close to its failure.